Ipsilateral anterior hip dislocation and posterior knee subluxation: A case report - Tanawat Vaseenon (2018)
Hip or knee dislocations are two orthopedic emergencies. Concomitant hip and knee dislocations are extremely rare. The authors report a case of ipsilateral anterior hip and posterior knee dislocations. Firstly, closed reduction of the knee and spanning external fixation was performed and then the hip was closely reduced under general anesthesia.